2019
DOI: 10.1371/journal.pone.0220922
|View full text |Cite
|
Sign up to set email alerts
|

The use of a 3D-printed prosthesis in a Great Hornbill (Buceros bicornis) with squamous cell carcinoma of the casque

Abstract: The advent of new technologies in medical imaging and 3D printing in recent years has made customization of surgical tools and implants more accessible, revolutionizing many surgical fields. In many human diseases, these implants have led to superior surgical outcomes and greatly improved patients’ quality of life. Thus, it is of great interest to apply these technologies to the treatment of animal diseases. In this study, we report the use of computed tomography (CT) and 3D printing for the treatment of a Gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 14 publications
1
3
0
2
Order By: Relevance
“…95,100 These neoplasms are commonly observed in numerous avian species. 1,2,[95][96][97][98][99][100][101][102][103][104][105][106][107][108] For parrots, our findings were in agreement with previous work, with 4 cases of SCC diagnosed in the uropygial gland and 1 as a dermal mass on the wing. In chickens, SCC occurs infrequently, but there have been reports of dermal lesions on the legs with a benign biological behavior that spontaneously resolve, 19 malignant generalized skin ulceration (avian keratoacanthoma), 109,110 and lesions in the oropharynx and upper gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 91%
“…95,100 These neoplasms are commonly observed in numerous avian species. 1,2,[95][96][97][98][99][100][101][102][103][104][105][106][107][108] For parrots, our findings were in agreement with previous work, with 4 cases of SCC diagnosed in the uropygial gland and 1 as a dermal mass on the wing. In chickens, SCC occurs infrequently, but there have been reports of dermal lesions on the legs with a benign biological behavior that spontaneously resolve, 19 malignant generalized skin ulceration (avian keratoacanthoma), 109,110 and lesions in the oropharynx and upper gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 91%
“…During the observation of the bird in its natural environment, no strange behaviors were observed, which suggests the acceptance by the bird of the 3D printed AFO as part of its own body. Xie et al achieved a similar result in a study on the use of a 3D printed prosthesis for a Great Hornbill (Xie et al, 2019). These positive results suggest great potential in applying these technologies to the treatment of other diseases and malformations in both farmed, domestic, and wild animals.…”
Section: Resultsmentioning
confidence: 74%
“…2,3 Previous studies have indicated the use of 3D software and using computer-assisted learning can benefit students in human medical education. [4][5][6] 3D printed materials have benefited animals' survival [7][8][9][10] and assisted in understanding canine brain anatomy, 11 jaw fractures, 12 vertebral fractures, 13 the equine limb, 14,15 and numerous instances of surgical planning. 16,17 Animated three-dimensional materials have been utilized for obstetrical problems in horses, 18 canine neuroanatomy, 19 canine larynx and hyoid apparatus, 20 and canine cruciate ligament rupture.…”
Section: Introductionmentioning
confidence: 99%